Implement completion and results report (IDA-29960, NETH-21604) on a credit in the amount of SDR15.9 million ( US (The World Bank, 2007)
Contents of the book is: Project contents, development objectives and design; project costs and financing; economic and financial analysis; beneficiary survey results.